(3QSGdI aj eSCdI GdcSH YfO GdCTYQjs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI hGdMeOdI hHYO ; aEfc PcQJ Cf eSCdI GdcSH hJejjRg GdPj gh GdePgH GdMb YfO GdePgHjf GdaGSOjf hgeG ePgHG GdLHQjI hGdbOQjI eeG GdJHS Ydjc aGYde hdOj Cfj CLeY dc ef cdGe GdCFeI GdeMbbjf eG jcTa GdZWGs
(3BNQgG (B:s
(3hjecf OaYg HGf GdeQGO Cf Gdecda Hg ChdG hHGdPGJ GdaYd HGdeYfi GdNGU HGdeUOQ adG jfGaj GdJcdja HGdaYd HGdeYfi GdeUOQj KGfjG hHGdJHY hchfg CeQG GYJHGQjG dG hLhO dg NGQLG dG jefY GdJcdja Hg JHYGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds